Factors predicting secondary school language course enrollment and performance among U.S. heritage speakers of Spanish - Nguyen, My V. H.; Serafini, Ellen J.; Leeman, Jennifer; Winsler, Adam (Frontiers in Psychology, 2023)
While a growing body of research indicates that Spanish language courses can promote Spanish maintenance and lead to overall improved educational outcomes among heritage speakers, there is little empirical or longitudinal evidence of factors that may shape their enrollment in Spanish language courses at the secondary level. To address this issue, the current study takes a large-scale, longitudinal approach to investigate rates of enrollment in secondary school (6th–12th grade) Spanish and other non-English language courses, as well as factors that predict heritage speakers’ enrollment and performance in non-English language courses. We analyzed subsample data from the Miami School Readiness Project (MSRP), a large-scale, longitudinal study consisting of 17,341 heritage speakers of Spanish (47% female, 95.4% Hispanic/Latino, 82.8% received free/reduced-price lunch, and 18.3% with a disability) who were followed from four years old until the end of high school. In general, students enrolled in Spanish language courses at a higher rate than other non-English language courses (52.2% and 25.3%, respectively). Enrollment patterns varied across different types of languages and grade levels. Student-level factors including disability status, poverty status, early behavioral problems, and prior academic achievement significantly predicted students’ enrollment in Spanish and performance in non-English language courses. Findings shed light on the long-term patterns of language study of this growing segment of the US school population with implications for future research and school policies that seek to improve heritage language learning and maintenance as well as equitable access to language education for language-minority students.